A fundamentalist perspective on accounting and implications for accounting research - Guohua Jiang; Stephen H. Penman (China Journal of Accounting Research, 2013)
This paper presents a framework for addressing normative accounting issues for reporting to shareholders. The framework is an alternative to the emerging Conceptual Framework of the International Accounting Standards Board and the Financial Accounting Standards Board. The framework can be broadly characterized as a utilitarian approach to accounting standard setting. It has two main features. First, accounting is linked to valuation models under which shareholders use accounting information to values their stakes. Second, the desirable characteristics of accounting information are inferred from the demand of investors and analysts who use the information in practice. This stands in contrast to the "qualitative characteristics" in the Boards' Framework which are embraced largely on the basis of their aesthetic appeal. These features lead to a set of broad accounting principles that resolve "recognition" and "measurement" issues at the core of the Boards' Conceptual Framework and also the central issue of a balance sheet approach versus an income statement approach. The framework in the paper also frames the research questions for researchers interested in accounting policy.
Keywords: 650